Weryfikacja modelu CAPM na podstawie jednoczynnikowego modelu GARCH dla GPW w Warszawie - Fiszeder, Piotr (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
Numerous studies have shown that conditional variances and covariances of returns are time-varying. Most of the CAPM and APT tests ignore those properties of financial time series. The variability of variances of factors and variances and covariances of asset returns may significantly influence the results of the tests. The APT model with the factor GARCH covariance structure, which is able to capture those properties of asset returns, is presented in the paper. In the empirical part of the paper, a test of the CAPM model is performed for sectors quoted on the Warsaw Stock Exchange. The procedure for testing the APT model with the one-factor GARCH model was applied. The results support the restrictions of the CAPM model, however none of the alternative specifications of the model are considered. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1176, s. 91-98